2018
DOI: 10.12972/kjhst.20180068
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Factors Influencing Growth and Ginsenoside Content of Panax ginseng Roots

Jinu Eo,
Hwang-Seong Mo,
Kee-Choon Park

Abstract: We aimed to evaluate the effects of abiotic factors on root growth and ginsenoside content of Panax ginseng and on the tradeoff between these two properties. Three experiments tested the effects of fertilization, soil particle size and cultivation site, respectively, on root growth and ginsenoside content. Moderate applications of nitrogen, phosphorus, and potassium did not significantly influence ginsenoside content. Root weight was negatively correlated with ginsenosides Rg1 and Rg2 with excessive fertilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…With the recent expansion in ginseng cultivation across Korea, there has been a tendency for excessive use of poultry, cattle, swine manure, and organic matter on farms, regardless of the existing soil fertility. This has consequently increased the occurrence of rusty root, a disease characterized by the development of yellowish brown or reddish-brown round or irregular spots on the root epidermis, which subsequently spreads to the entire root (Eo et al, 2018). If this occurs in 1-or 2-year-old plants, it can inhibit root thickening, whereas in plants older than 4 years, the root epidermis becomes rougher or, in severe cases, develops cracks (Hong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…With the recent expansion in ginseng cultivation across Korea, there has been a tendency for excessive use of poultry, cattle, swine manure, and organic matter on farms, regardless of the existing soil fertility. This has consequently increased the occurrence of rusty root, a disease characterized by the development of yellowish brown or reddish-brown round or irregular spots on the root epidermis, which subsequently spreads to the entire root (Eo et al, 2018). If this occurs in 1-or 2-year-old plants, it can inhibit root thickening, whereas in plants older than 4 years, the root epidermis becomes rougher or, in severe cases, develops cracks (Hong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the future, if a study on the soil microbial community in various WSG cultivation areas is conducted, it is thought that the cause of the change in the available phosphate content can be identified. Eo et al [25] reported that fused calcium magnesium phosphate (17% phosphorus) can enhance the growth of WSG. They explained that phosphorus could greatly affect the growth of WSG.…”
Section: Growth Characteristics and Ginsenoside Contents Of Wsg With ...mentioning
confidence: 99%